New classification system for pediatric glaucoma: implications for clinical care and a research registry. Issue 5 (September 2018) - Thau, Avrey; Lloyd, Maureen; Freedman, Sharon; Beck, Allen; Grajewski, Alana; Levin, Alex V.
Abstract : Purpose of review: The Childhood Glaucoma Research Network (CGRN) has created a new classification system for childhood glaucoma that has become the first International Consensus Classification. The purpose of this review is to present this classification system and share its use to date. Recent Findings: The diagnoses of the classification system include glaucoma and glaucoma suspect. The primary glaucomas include: primary congenital glaucoma and juvenile open-angle glaucoma. The secondary glaucomas include: glaucoma following cataract surgery, glaucoma associated with nonacquired systemic disease or syndrome, glaucoma associated with nonacquired ocular anomalies, and glaucoma associated with acquired conditions. This system reached consensus agreement at the Ninth World Glaucoma Association Consensus, which has been adopted by the American Board of Ophthalmology, and has been implemented in outcomes research, incidence studies, and review articles. The new Robison D. Harley, MD CGRN International Pediatric Glaucoma Registry uses this classification system as a shared language, allowing international clinicians and researchers to collaborate and make large-scale investigations of this otherwise rare disease possible. Summary: The diagnoses in this system are assigned by following a logical and systematically approachable path. The ability to easily adopt and implement the system lends itself to international research.